The european digital single market and artificial intelligence : impacts on the banking industry : the case of Montepio - Schwind, Julian Clemens (2020)
In 2015, Jean-Claude Juncker, former President of the European Commission, announced the Digital Single Market (DSM) strategy with the goal to create a digitally connected European continent. Since then, European authorities started to remove online barriers and joined forces to become interconnected between people and corporations. This fosters the digital transformation process of all European businesses, leads to a digital European society and makes Europe more competitive in a global perspective. Within the DSM, artificial intelligence (AI) is a crucial cornerstone as it improves operations, optimizes process efficiencies and results in cost savings for Europe’s firms. This thesis was developed as a consulting project at Montepio, a Portuguese bank. Impacts of the DSM and AI on the banking industry were assessed. Expert interviews with digital banking specialists were conducted to examine practical AI use cases in banks. Furthermore, secondary data compiled by a literature search on DSM initiatives in Europe and additional AI use cases in banking were analyzed. As the completion of the DSM is in proximity, it is recommended that Montepio broadens its digital footprint to benefit from the intensified digital collaboration in Europe and use synergies on a supranational level. Today, most organizations started applying AI in their banking operations and follow a human-centric AI approach. Montepio is on a good way with its first AI application called MARIA. However, the bank should further develop AI practices to stay at the forefront of the digital transformation process in Europe and to be competitive in the future.